Calciphylaxis in a Patient With Non-Hodgkin Lymphoma: Case Report and Literature Review. Issue 5 (September 2018) - Morand, Meggie; Chababi-Atallah, Myrna; Jean, Sara-Élizabeth; Fernandes, Carolina
Background: Calciphylaxis is a well-known entity in end-stage kidney disease and after renal transplant. Cases of nonuremic calciphylaxis (NUC) have also been reported, but data on this rare condition are mainly empirical. Objective: We discuss a case of NUC secondary to spontaneous tumour lysis syndrome in a patient who had chemotherapy for non-Hodgkin lymphoma and present a review of the literature to better characterize malignancy-associated NUC. Methods: We identified 12 published cases of malignancy-associated NUC. Results: This systematic review of malignancy-associated NUC did not show a relationship between the type of malignancy, the distribution of skin lesions, or mortality. However, distal more than proximal involvement seems to be more frequently associated with calcium phosphate imbalance. Conclusion: Clinicians must maintain a high index of suspicion for calciphylaxis when evaluating patients with cutaneous lesions developed in the setting of malignancy.